MODEL PEMBERDAYAAN HUKUM UNTUK PENGELOLAAN GOA PINDUL BERKELANJUTAN - Rismawati, Shinta Dewi; Azkiya Thoha, Silvia Milady; Sumbogo, Yuliarto Joko; Sasongko, Supomo Ari (LPPM Universitas Bina Bangsa, 2025)
The existence of Pindul Cave has led to ongoing conflicts due to the involvement of multiple parties. This paper aims to analyze the underlying causes of conflict in the management of Pindul Cave and propose legal empowerment strategies to reduce these conflicts, using a legal systems theory approach. The research employs an empirical juridical methodology, focusing on a case study of Pindul Cave management, and gathers both primary and secondary data through interviews, observations, and documentation studies. The data analysis is conducted using an interactive model. The findings reveal that the primary source of conflict in the management of Pindul Cave tourism stemmed from a land ownership dispute between Atiek Damayanti and the previous tourism manager. This dispute escalated, involving multiple parties on a relatively large scale. The conflict was primarily fueled by a power struggle over the management of Pindul Cave. To address these issues, the legal empowerment model, approached from a legal systems perspective, suggests that by considering the law as an integrated system incorporating legal substance, structure, and culture. It may be possible to reduce conflicts in the management of Pindul Cave as a natural tourist attraction.